KEPUASAN KERJA GURU MDA (MADRASAH DINIYAH AWALIYAH) DI KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Utari, R.A Maulida; Baheram, Murni; Bahar, Aswandi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was motivated by the lack of job satisfaction of teachers whoteach MDA in Sub Tuah Karya Tampan District of Pekanbaru The research problems arehow high job satisfaction of teachers MDA in Sub Tuah work Handsome District of the cityof Pekanbaru. The purpose of this study was to determine the level of job satisfaction ofteachers MDA in Sub Tuah work Handsome District of the city of Pekanbaru. Thepopulation in this study is as much as 55 people. The technique used in this study isNonrobability sampling and sampling methods that use saturated sample,. Instrumentcollecting data questionnaire with 64 statements. Data were analyzed by DescriptiveQuantitative analysis. From the results of data analysis showed that MDA teacher jobsatisfaction in the Sub Tuah Karya Tampan District of Pekanbaru is high.Keywords: Job Satisfaction, Job Satisfaction Guru, MDA (Madrasah Diniyah Awaliyah)